Relationship between Demographic Characteristics, Knowledge and Attitude of Fertile Aged Women in Seeking Pap Smear Services at Sukawati II Community Health Centre, Gianyar Regency - Martini; Luh Putu Lila Wulandari; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Pap smear coverage in 2011 at Sukawati II Health Centre was only 0.39% (17 people) which is well below the district target of 85%. This is in fact a decrease from 2009 (1.12%/49 people) and 2010 (0.73%/32 people). This study was aimed to examine the relationship between demographics, knowledge, and attitudes of reproductive aged women, including sexual behavior and pap smear seeking behavior. Methods: Research used a cross-sectional survey among 50 reproductive aged women from Sukawati II Health Center, not pregnant and literate. Data was collected through structured questionnaire interview and secondary data from healthcare center records. Data were analysed using univariate, bivariate (chi-squared test) and multivariate analysis (logistic regression). Results: Bivariate analysis indicated that education (p=0.006), financial status (p=0.024), knowledge (p=0.006) and attitude (p=0.001) were significantly associated with pap smear practices. The multivariate analysis showed that onlythe attitude ofwomen that related toactionswith apap smearwith OR=12 (95%CI: 2.31-62.46). Conclusion: The attitude of reproductive aged women is associated to pap smear practices in Sukawati II Health Centre, Gianyar Regency.